Corporate social reporting in Singapore. - Ong, Wei Han. (2008)
With the arrival of the 21st Century, corporations are no longer seen as a stand-alone profit-making entities. Increasingly, they are perceived by society as corporate citizens who owe a duty to the society. As a result, there is a need for corporations to engage in socially responsible activities in order to stay legitimate in the present environment.The report looks at the current state of Corporate Social Reporting in Singapore. Specifically, the nature and extent of Corporate Social Reporting, the relationship between specific firm attributes and Corporate Social Reporting as weell as the reporting trend of two industries.